PENGARUH KUALITAS PRODUK, HARGA, DAN PROMOSI TERHADAP LOYALITAS PELANGGAN KARTU PRABAYAR TELKOMSEL (Studi Kasus Pada Mahasiswa STIE Muara Teweh) - Noorhayati Noorhayati (Jurnal Ekonomi dan Manajemen, 2018)
The result showed that : 1) quality of product (X1), price (X2), and promotion (X3) has a simultan impact on customers loyalty at Telkomsel pre-paid card, this is evidenced by the results calculations F statistics the three of variable 18.048 (sig. 0.000) is greater than F table is 2.76 with alpha 5 %. 2) quality of product (X1) has a significant impact on customers loyalty at Telkomsel pre-paid card, this is evidenced by the results calculations t statistics 3.697 (sig. 0.000) is greater than t table is 2.000 with alpha 5 %. price (X2) has a significant impact on customers loyalty at Telkomsel pre-paid card, this is evidenced by the results calculations t statistics 4.000 (sig. 0.000) is greater than t table is 2.000 with alpha 5 %. While promotion (X3) has not a significant impact on loyalty at Telkomsel pre-paid card, this is evidenced by the results calculations t statistics -0.411 (sig. 0.683) is smaller than t table is 2.000 with alpha 5 %. 3) the most dominan variable affecting customers loyalty at Telkomsel pre-paid card is quality of product (X1) and price (X2).